2022
DOI: 10.1007/s13201-022-01847-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different managements with drip irrigation (tape)

Abstract: Conventional irrigation methods to new methods have been altered with respect to reduction of water resources and climate change. Considering the corn cultivation development, applying modern irrigation methods namely drip irrigation with the aim of improving the efficiency of water consumption as well as the zone under cultivation has been investigated. In this research, the performance of corn (SC 704) in various managements of drip irrigation (by strip method) both in single-row and double-row planting patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The highest recorded single pod weight was 10.92 g in T4, with T3 and T2 following at 9.48 g and 8.16 g respectively. The lowest weight was observed in T1 at 7.56 g. Other researchers conducting field experiments have found similar results to those reported here, as noted in citations [4,17].…”
Section: Single Pod Weight (G)supporting
confidence: 91%
See 1 more Smart Citation
“…The highest recorded single pod weight was 10.92 g in T4, with T3 and T2 following at 9.48 g and 8.16 g respectively. The lowest weight was observed in T1 at 7.56 g. Other researchers conducting field experiments have found similar results to those reported here, as noted in citations [4,17].…”
Section: Single Pod Weight (G)supporting
confidence: 91%
“…Irrigation water, nutrients, and runoff can be efficiently controlled and used by installing drip irrigation systems in the field. It decreases the evaporation of water from the field by decreasing runoff and providing water to the root area [4]. Drip irrigation applies water directly to the plant or crop near its stem region and soil surface.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that PRD-treated plots significantly reduced water usage and increased water use efficiency by 60 %. Amini et al (2023) have tested the performance of corn (SC 704) in drip irrigation (by strip method) with a different density and different row planting pattern. Results showed that applying drip tapes and different surface treatments with soil and water monitoring reduced water consumption by 81 %, 71 %, 61 %, 52 % and 36 %.…”
Section: Best Management Practices For Implementing Micro Irrigationmentioning
confidence: 99%
“…Generally, thickened drip irrigation belts are used abroad, and due to the better natural environment compared to Xinjiang, their aging problem is not so prominent and can be used multiple times. Researchers' research on this type of drip irrigation belt mainly focuses on the impact of irrigation parameters on the professional performance of drip irrigation belts, and so on 25 . Therefore, there are currently no research results that can be directly referenced in the aging characteristics of drip irrigation belts and their impact on mechanized recycling, and reuse in Xinjiang cotton fields where low-cost thin drip irrigation belts are used.…”
Section: Introductionmentioning
confidence: 99%